Bilateral Surgically Induced Necrotizing Scleritis After Pterygium Excision with Conjunctival Autograft: A Case Report - Hamzeh Mohammad Alrawashdeh; Omar Al-Habahbeh (Oman Medical Journal, 2022)
Surgically induced necrotizing scleritis (SINS) is an immune-mediated condition that rarely occurs after ocular surgeries with a latency period of days to years. We present a case of a 49-year-old man who developed bilateral SINS two weeks after uneventful bilateral pterygium excision with conjunctival autografts. He was managed with a course of oral prednisolone, topical antibiotic ointment, topical non-steroidal anti-inflammatory drugs and lubricants, and close follow-up and rheumatological consultation.